Urgensi Pendampingan Orang tua pada Pendidikan Anak Masa Darurat Covid-19 - Afida Nurriqi; Nur Ziadatul Hasanah (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2021)
This studi to find out how parental assistane is to children during covid 19. The research method used is qualitative reseacrh whice is a study conducted to find out a realiy that occurs in the field. With conditions as they are, not conditions they should be. The results of this study are many paprents who already know about online learning, but there are many obstacles faced by parents including the data quota to acces the internet which is used for online learning. It can be said that online learnig is wasteful in using internet data quota, the limited ability of parents in understand the material provided by the teacher so that it is not clear to the child, the monotonous parental explanation also makes the child bored.